To the issue of prevention of acute vessel optic neuropathy - Konovalova, N. V.; Naritsyna, N. I.; Serebrina, T. M.; Reznichenko, A. L. (Ukrainian Journal of Ophthalmology, 2026)
Vascular pathology of the eye is one of the leading causes of blindness. Diseases caused by circulatory disorders constitute 10—15 % of all eye diseases. Purpose — to examine the preventive effect of lutein and zeaxanthin on the basis of clinical examination of patients with chronic vascular pathology. The possibility of acute vascular neuropathy for example, 57 patients (114 eyes) with chronic ischemic neuropathy of the optic nerve that within 3 months of receiving lutein and zeaxanthin, the control group consisted of 35 patients (70 eyes) who received no prophylactic treatment and in 3 patients (3 eyes) occurred venous occlusion and arterial occlusion of the vessels of the optic nerve. Conclusions. Use of lutein and zeaxanthin is preventing the emergence and development of acute retinal vascular occlusion. Patients who did not receive prophylactic treatment (4,28 %). Getting the vascular occlusion optic nerve.